Advantages and Limitations of SNP Array in the Molecular Characterization of Pediatric T-Cell Acute Lymphoblastic Leukemia - Lejman, Monika; Włodarczyk, Monika; Styka, Borys; Pastorczak, Agata; Zawitkowska, Joanna; Taha, Joanna; Sędek, Łukasz; Skonieczka, Katarzyna; Braun, Marcin; Haus, Olga; Szczepański, Tomasz; Młynarski, Wojciech; et al. (Frontiers in Oncology, 2020)
T-cell acute lymphoblastic leukemia (T-ALL) is a highly heterogeneous disease, and numerous genetic aberrations in the leukemic genome are responsible for the biological and clinical differences among particular ALL subtypes. However, there is limited knowledge regarding the association of whole-genome copy number abnormalities (CNAs) in childhood T-ALL with the course of leukemia and its outcome. The aim of this study was to identify the pattern of whole-genome CNAs in 86 newly diagnosed childhood T-ALL cases using a high-density single-nucleotide polymorphism (SNP) array. We analyzed the presence of whole-genome CNAs with respect to immunophenotype, clinical features, and treatment outcomes. A total of 769 CNAs, including trisomies, duplications, deletions, and segmental loss of heterozygosity, were detected in 86 analyzed samples. Gain or loss of chromosomal regions exceeding 10 Mb occurred in 46 cases (53%), including 6 cases (7%) with complex chromosomal alterations. We observed that microdeletions in selected genes (e.g., FIP1L1 and PDGFRB) were related to the clinical features. Interestingly, 13% of samples have a duplication of the two loci (MYB and AIH1 - 6q23.3), which never occurred alone. SNP array significantly improved the molecular characterization of pediatric T-ALL. Further studies with larger cohorts of patients may contribute to the selection of prognostic CNAs in this group of patients.